Comparisons between EDI and ebXML Architecture in Business to Business (B2B) Electronic Commerce (EC) / Fitriasrah Razali - Razali, Fitriasrah (Faculty of Computer and Mathematical Sciences, 2007)
For over 25 years, organizations have used Electronic Data Interchange (EDI) systems to handle business transaction. However, EDI is neither cheap nor simple and is based on private network such as Value Added Network (VAN) .It forces organization into long term, tightly coupled trading relationship with their business partners. EDI also does not stand for free exchanging infomnation and transaction. As e-Business frameworks have evolved from traditional EDI technology to Internet using EDI, it is still not mature enough to allow their broad successful commercial application. All these approaches lack substantial reflection and integration of business semantic as the basic of any electronic commerce partnership. ebXML is a world-wide initiative that tries to solve drawbacks of existing standard and approaches and has the potential to successfully delivery solutions to these problems. Therefore, in this paper, researcher is trying to compare both applications respectively. The comparison will be based on criterion with regard to business architecture since this work focus on B2B application. Researcher gathers information by having an inten/iew with an expert in this field instead make critical analysis based on previous journals and other studies. As a result, EDI is obviously stay back behind the ebXML as it can also fulfill the functionality of EDI and developed based on the investment in and experiences of EDI.